Ethics and informatics in the age of COVID-19: challenges and recommendations for public health organization and public policy. (28th July 2020) - Subbian, Vignesh; Solomonides, Anthony; Clarkson, Melissa; Rahimzadeh, Vasiliki Nataly; Petersen, Carolyn; Schreiber, Richard; DeMuro, Paul R; Dua, Prerna; Goodman, Kenneth W; Kaplan, Bonnie; Koppel, Ross; Lehmann, Christoph U; et al.
Abstract: The COVID-19 pandemic response in the United States has exposed significant gaps in information systems and processes that prevent timely clinical and public health decision-making. Specifically, the use of informatics to mitigate the spread of SARS-CoV-2, support COVID-19 care delivery, and accelerate knowledge discovery bring to the forefront issues of privacy, surveillance, limits of state powers, and interoperability between public health and clinical information systems. Using a consensus-building process, we critically analyze informatics-related ethical issues in light of the pandemic across 3 themes: (1) public health reporting and data sharing, (2) contact tracing and tracking, and (3) clinical scoring tools for critical care. We provide context and rationale for ethical considerations and recommendations that are actionable during the pandemic and conclude with recommendations calling for longer-term, broader change (beyond the pandemic) for public health organization and policy reform.